2004
DOI: 10.1037/0022-3514.87.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Social Inference: A Similarity Contingency Model of Projection and Stereotyping in Attribute Prevalence Estimates.

Abstract: Most models of how perceivers infer the widespread attitudes and qualities of social groups revolve around either the self (social projection, false consensus) or stereotypes (stereotyping). The author suggests people rely on both of these inferential strategies, with perceived general similarity moderating their use, leading to increased levels of projection and decreased levels of stereotyping. Three studies featuring existing individual differences in perceived similarity as well as manipulated perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
293
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(311 citation statements)
references
References 42 publications
16
293
0
2
Order By: Relevance
“…Predictions can be made either by projection, whereby information about oneself is used to make an inference about another person, or by stereotyping, whereby information about a group that that individual belongs to is used in making inferences. Judgments of similarity likely play a role here, since people are more likely to use projection with individuals who are similar to themselves and stereotyping with individuals who are dissimilar (Ames, 2004). Exploring children's reasoning about similarity to others should thus provide insight into how they form expectations about individuals and also increase our knowledge of the early roots of person perception.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions can be made either by projection, whereby information about oneself is used to make an inference about another person, or by stereotyping, whereby information about a group that that individual belongs to is used in making inferences. Judgments of similarity likely play a role here, since people are more likely to use projection with individuals who are similar to themselves and stereotyping with individuals who are dissimilar (Ames, 2004). Exploring children's reasoning about similarity to others should thus provide insight into how they form expectations about individuals and also increase our knowledge of the early roots of person perception.…”
Section: Discussionmentioning
confidence: 99%
“…Different activities might produce different results. For example, Ames (2004) found that individuals are more likely to use social projection with others that they believe are generally similar to the self and more likely to use stereotypes with others that are believed to be generally dissimilar. It is possible that in a social context in which subjects did not feel particularly connected to others, they may have relied more heavily on preexisting stereotypes-perhaps producing clearer generalized-other effects as a result.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…General assumed similarity would be evidenced by a positive correlation between selfperceptions and perceiver effects. (A belief that the self is similar to some and dissimilar to others, as in Ames, 2004, would affect correlations with relationship effects.) Several studies in which the SRM has been used have found evidence of general assumed similarity-that is, correlations between self-perceptions and perceiver effects-in personality trait perceptions.…”
Section: Perceiver Effects and The Self: Trait Specificity In Assumedmentioning
confidence: 99%
“…Therefore, we measured attitudes towards theft was by assessing the acceptability dimension of attitudes towards theft, measured on a 7-point likert-type scale ranging from "very unacceptable" to "very acceptable". In addition to acceptability judgments, research has also found that an individual uses projections of their own attitudes when making inferences about the attitudes of someone else (e.g., Ames, 2004;Goel, Mason, & Watts, 2010). That is, an individual's inference about another person's attitude towards theft may be an indirect measure of their own attitude towards theft without linking the behavior directly to themselves.…”
Section: Procedures and Materialsmentioning
confidence: 99%